2018
DOI: 10.1504/gber.2018.090091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of firm specific and macroeconomic factors on financial performance of the UAE insurance sector

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
3
12
0
1
Order By: Relevance
“…A good and conducive economic condition which is represented by the amount of GDP which continues to increase in a sustainable manner will encourage the increased financial performance of life insurance companies. This finding is in line with Meher & Zewudu (2020) in Ethiopia, Alomari & Azzam (2017) in Jordan, Pradhan & Pokharel (2020) in Nepal, Banerjee & Majumdar (2018) in the UEA, and Batool & Sahi (2016) in the US and the UK. However, it is different from what happened in the Philippines (Cudiamat &Siy, 2017), andin Pakistan (Shawar &Siddiqui, 2019) where the financial performance of insurance companies, both life and general, is not influenced by GDP.…”
Section: Inferential Statistical Analysis: Panel Data Regression Anal...supporting
confidence: 87%
See 1 more Smart Citation
“…A good and conducive economic condition which is represented by the amount of GDP which continues to increase in a sustainable manner will encourage the increased financial performance of life insurance companies. This finding is in line with Meher & Zewudu (2020) in Ethiopia, Alomari & Azzam (2017) in Jordan, Pradhan & Pokharel (2020) in Nepal, Banerjee & Majumdar (2018) in the UEA, and Batool & Sahi (2016) in the US and the UK. However, it is different from what happened in the Philippines (Cudiamat &Siy, 2017), andin Pakistan (Shawar &Siddiqui, 2019) where the financial performance of insurance companies, both life and general, is not influenced by GDP.…”
Section: Inferential Statistical Analysis: Panel Data Regression Anal...supporting
confidence: 87%
“…The findings of Pradhan & Pokharel (2020) are in accordance with the above-mentioned studies where, in Nepal, financial performance of life insurance was positively influenced by GDP-growth. In the United Arab Emirates, Banerjee & Majumdar (2018) uncovered the same empirical evidences which indicates that GDPgrowth affects financial performance of insurance companies in a positive way. In the US and UK, Batool & Sahi (2016), identified that financial performance of insurance companies in these countries was influenced positively by GDP-growth.…”
Section: The Determining Factors Of Profitability Of Life Insurancementioning
confidence: 73%
“…For Banerjee and Majumdar (2018), the economic crisis of 2007-2008 witnessed a failure for growth rates in UAE insurance sector. The research focuses on the fiscal performance of the insurance segment post-global economic crisis for the period 2009-2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also supported on a finding by Kulustayeva, Jondelbayeva, Nurmagambetova, Dossayeva and Bikteubayeva (2020) on a negative significant relationship towards profitability. Furthermore, insurance companies must keep adequate and suitable technical reserves based on the nature of their potential liabilities (Banerjee & Majumdar, 2018). However, Mohamad Said, Abdull Rahman, Abd Mutalib, and Badri (2021) identified that leverage and size of the respected sample of Malaysian hotel industry have a statistically significant relationship with profitability.…”
Section: Literature Reviewmentioning
confidence: 99%